Cluster analysis for symptomatic management of Neisseria gonorrhoea and Chlamydia trachomatis in sexually transmitted infections related clinics in China - Ning, Ning; Weng, Rongxing; Zhang, Chunlai; Wen, Lizhang; Wang, Honglin; Ye, Jianbin; Li, Jing; Chen, Xiangsheng; Cai, Yumao (Frontiers in Public Health, 2022)
Objective This study aimed to perform a cluster analysis of symptoms linked with Neisseria gonorrhoeae (NG) and Chlamydia trachomatis (CT) and to identify which cluster of symptoms was associated with a higher risk of NG and CT. Study design From 15 April to 16 May 2018, a cross-sectional study was conducted, and patients attending sexually transmitted infections (STI) related clinics were recruited from 22 medical institutions in six districts of Shenzhen city. Methods A structured questionnaire was used to collect social-demographic information as well as STI symptoms, and urine samples were collected for nucleic acid detection. Cluster analysis and logistic regression were applied. Results Among 8,207 participants, the prevalence of CT and NG infection was 9.04% (742/8,207) and 2.36% (194/8,207), respectively. Among male outpatients, four clusters with distinct symptomatic patterns were identified. Unmarried, having casual sexual partners in the past 6 months, cluster 2 (OR = 6.70, 95% CI = 3.36–13.35) and cluster 4 (OR = 24.53, 95% CI = 12.96–46.44) were risk factors associated with NG infection. Unmarried, cluster 2 (OR = 2.54, 95% CI = 1.83–3.53) and cluster 4 (OR = 3.31, 95% CI = 2.37–4.61) were risk factors associated with CT infection. Among female outpatients, five clusters with distinct symptomatic patterns were identified. Aged 24 years or below and cluster 3 (OR = 3.68, 95% CI = 1.61–8.39) were risk factors associated with NG infection. Aged 24 years or below, unmarried, having a high school/secondary technical school education, and having junior high school or below education were risk factors associated with CT infection. Conclusion The cluster of symptoms integrated into risk assessment for CT and NG infections suggests a new strategy of symptomatic management. Healthcare providers in STI clinics and resource-limited places may use this strategy to identify more potential patients and deliver adequate, acceptable, and equitable STI care for outpatients with a high risk of STI.